2012
DOI: 10.1103/physrevd.86.043008
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic theory of collisionless self-gravitating gases. II. Relativistic corrections in galactic dynamics

Abstract: In this paper we study the kinetic theory of many-particle astrophysical systems imposing axial symmetry and extending our previous analysis in Phys. Rev. D 83, 123007 (2011).Starting from a Newtonian model describing a collisionless self-gravitating gas, we develop a framework to include systematically the first general relativistic corrections to the matter distribution and gravitational potentials for general stationary systems. Then, we use our method to obtain particular solutions for the case of the Morg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 77 publications
(98 reference statements)
1
31
0
1
Order By: Relevance
“…These small numbers suggest that GR corrections to Newtonian dynamics, namely on the rotation curve (RC), are smaller than 1%, and therefore significantly smaller than the typical uncertainties associated with the astrophysical data from galaxies. Some authors agree with the assumption of using GR in galaxies (item i), but found that those small numbers in the items ii and iii may lead to significative consequences on dark matter distribution in galaxies and corrections to the RCs larger than 10% (Cooperstock & Tieu 2007;Carrick & Cooperstock 2012;Magalhaes & Cooperstock 2015;Balasin & Grumiller 2008;Ramos-Caro et al 2012). The CT approach (Cooperstock & Tieu 2006Carrick & Cooperstock 2012;Magalhaes & Cooperstock 2015) has received a number of criticisms on the theoretical basis, which the authors claim to have answered (Carrick & Cooperstock 2012).…”
Section: General Considerationsmentioning
confidence: 95%
“…These small numbers suggest that GR corrections to Newtonian dynamics, namely on the rotation curve (RC), are smaller than 1%, and therefore significantly smaller than the typical uncertainties associated with the astrophysical data from galaxies. Some authors agree with the assumption of using GR in galaxies (item i), but found that those small numbers in the items ii and iii may lead to significative consequences on dark matter distribution in galaxies and corrections to the RCs larger than 10% (Cooperstock & Tieu 2007;Carrick & Cooperstock 2012;Magalhaes & Cooperstock 2015;Balasin & Grumiller 2008;Ramos-Caro et al 2012). The CT approach (Cooperstock & Tieu 2006Carrick & Cooperstock 2012;Magalhaes & Cooperstock 2015) has received a number of criticisms on the theoretical basis, which the authors claim to have answered (Carrick & Cooperstock 2012).…”
Section: General Considerationsmentioning
confidence: 95%
“…González, Plata & Ramos-Caro (2010) start from the observational data of four galaxies and construct models with the corresponding densities and potentials. The effects of relativistic corrections are studied in (Ramos-Caro, Agn & Pedraza 2012, Nguyen & Lingam 2013, and a model motivated by renormalization group corrections is investigated in (Rodrigues, Letelier & Shapiro 2010). Rotation curves obtained in alternative gravitational theories such as Modified Newtonian Dynamics (MOND) and Scalar-Tensor-Vector Gravity (STVG) can be found in (Famaey & McGaugh 2012) The outline of the present paper is as follows.…”
Section: Introductionmentioning
confidence: 99%
“…The stability of circular geodesics in smooth axially symmetric stress-energy distributions was first considered in [12], in which some remarks about their vertical stability in the limit of an infinitesimally thin disk are presented. During the last decades, many exact solutions representing thin disks were obtained, both in GR (see for example [13][14][15][16][17][18][19][20] and the reviews [4,5]) and in modified theories of gravity [21,22], mainly based * rss.vieira@usp.br † javier@ufscar.br ‡ asaa@ime.unicamp.br on the formalism of distribution-valued curvature tensors proposed by Taub [23]. For razor-thin disks, such an approach is consistent with the results about distributional sources in general relativity obtained by Geroch and Traschen [24], which provide an adequate framework to deal with distribution-valued curvature tensors with support on spacetime hypersurfaces.…”
Section: Introductionmentioning
confidence: 99%